NATIONAL ISLAM IN THE CONTESTATION OF IDEOLOGY AND POLITICS IN INDONESIA - Khamdan, Muhammad; Wiharyani, Wiharyani; Abidin, Nadiah (Ulul Albab: Jurnal Studi Islam, 2024)
This article explores the contestation of ideology and commodification of identity within Indonesia’s political democracy. The interplay between religion and the state presents significant challenges, influencing political movements aligned with religious convictions. Employing a political sociology approach, this study examines the contention between factions advocating for the integration of religion and the state and those supporting their separation. Additionally, the analysis considers the relationship between identity commodification and ideological contestation, highlighting Pancasila’s role as a national consensus. A qualitative methodology provides in-depth insights, incorporating content and descriptive analysis to process information from various documents. Primary materials for this research encompass documents related to Pancasila values, identity commodification, and political contestation. The politicization of identity in Indonesia, characterized by the dichotomy between nationalist Islam and secular nationalism, is depicted as a strategic maneuver aimed at achieving power dominance. There are three political groups that will continue to color Indonesian politics because they have different perceptions of the relationship between religion and the state: Islamist groups who want to unite religion and state, secular groups who want to separate religion and state, and accommodative groups who place religion as a source of ethics and the moral basis of policy.